2006
DOI: 10.1103/physrevlett.97.186405
|View full text |Cite
|
Sign up to set email alerts
|

Completed-Band Dispersion Relation in Sodium Cobaltates

Abstract: We utilize fine-tuned polarization selection coupled with excitation-energy variation of photoelectron signal to image the complete d-band dispersion relation in sodium cobaltates. A hybridization gap anticrossing is observed along the Brillouin zone corner and the full quasiparticle band is found to emerge as a many-body entity lacking a pure orbital polarization. At low dopings, the quasiparticle bandwidth (Fermion scale, many-body E F 0:25 eV) is found to be smaller than most known oxide metals. The low-lyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
55
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 26 publications
16
55
1
Order By: Relevance
“…The preceding ARPES experimental results confirmed that the top postion of the e g band is doping independent, sinking below the Fermi energy, suggesting that it plays no role in the lowenergy phenomena [13][14][15][16][17][18][19][20] . The combined these ARPES experimental results [13][14][15][16][17][18][19][20] and the transport experimental data 6-10 therefore show that the essential low-energy physics of the cobaltates is dominated by the strong electron correlation. The strong-coupling Hubbard model and its equivalent, the t-J model, are prototypes to study the strong correlation effects in solids, especially in connection with the unconventional superconductivity 21,22 .…”
Section: Electron Momentum Distributionsupporting
confidence: 70%
See 3 more Smart Citations
“…The preceding ARPES experimental results confirmed that the top postion of the e g band is doping independent, sinking below the Fermi energy, suggesting that it plays no role in the lowenergy phenomena [13][14][15][16][17][18][19][20] . The combined these ARPES experimental results [13][14][15][16][17][18][19][20] and the transport experimental data 6-10 therefore show that the essential low-energy physics of the cobaltates is dominated by the strong electron correlation. The strong-coupling Hubbard model and its equivalent, the t-J model, are prototypes to study the strong correlation effects in solids, especially in connection with the unconventional superconductivity 21,22 .…”
Section: Electron Momentum Distributionsupporting
confidence: 70%
“…The first principle band calculations predict that the cobaltates have a large EFS centered around the Γ point of the Brillouin zone (BZ) and six small pockets near the K points 11 . However, the angleresolved photoemission spectroscopy (ARPES) measurements on the cobaltates reveal only the large EFS [12][13][14][15][16][17][18][19][20] , while six small EFS pockets near the K points are absent. In particular, these ARPES experimental data also indicate that the area of EFS contains 1 + δ electrons, and therefore fulfills Luttinger's theorem 15,18,20 , where δ is the electron doping concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study sees a significant z-dispersion resulting in additional FS segments 15 while in most cases the system seems to remain quasi-2D 14,30 . If additional Fermi surface caused by threedimensionality was present, a higher DOS is consequently to be expected.…”
Section: Comparing Cp Arpes and Band Structure Calculationsmentioning
confidence: 99%